Knowledge, attitude, and practice on food label use among university students - Md Zaini, Syahirah; Ibrahim, Muhamad Ariff; Saad, Nurulwahida; Mohd Nazori, Mohd Nazir; Shamsuddin, Aida Soraya (IIUM Press, 2022)
Introduction: Choosing the right food product suitable for consumers are important to control the intake of additional and altered ingredients to avoid the risk of Non- Communicable Diseases (NCDs). Food labels guide consumers in deciding on healthy food products byproviding accurate information regarding specific product characteristics including the nutritional contents. The main objective of this study was to assess the knowledge, attitude, and practice regarding food labelling among students of IIUM. Method: Cross-sectional study was conducted on 418 students from Gombak, Kuantan, Gambang and Pagoh campuses. A set of questionnaires was designed consisting of five sections: sociodemographic, knowledge on foodlabel, attitude towards food labels, practice of food label and, factor influencing food label use. Result: Only one significant correlation was found between scores of attitudes and practice of food label (p < 0.01). Respondents showed positive attitude level obtained by 82.3% of respondents (n = 344) and 56.2% (n = 235) were good users of food label, while 61.5% (n = 257) had high knowledge level of food label. However, no significant differences were found in KAP food label across gender and educationlevel. Conclusion: Findings could be useful in the promotion and awareness of food label use among tertiary students in the future.